Valorization and Analysis of Flax Traits in Selected Accessions of Diversified Origin from the Linum usitatissimum L. Genetic Resources Collection - Grażyna Silska; Maria Mackiewicz-Talarczyk; Tomasz Górecki (Journal of Natural Fibers, 2022)
Genetic resources of flax from different geographical regions have been gathered in Poland since the 1930s. The aim of the research was to evaluate morphological and agricultural traits of 20 flax accessions, to determine the ranges of variability, and to develop the results in the form required for International Flax Database (IFDB) development. Obtained data were statistically analyzed using ANOVA with post hoc tests (least significant differences), canonical correlations, and Mahalanobis distances. The results of the analysis (ANOVA) proved that five traits of flax varieties differ significantly: plant height, technical length, slenderness, 1000 seeds weight, and seed yield. The ranges of variability of flax genotypes: total plant length: 58.05 cm−92.8 cm; technical length: 44.7–78.6 cm; stem thickness: 1.42–2.18 mm; slenderness: 246–474; panicle length: 10.05–21.55 cm; number of panicle branches: 3.4–6.2; number of capsules per plant: 5.15–19.7; number of seeds in capsule: 6.24–7.86; 1000 seeds weight: 4.82 g − 7.72 g. The results of the investigation could provide an important step of initial material selection for breeding of new varieties as well as information for entrepreneurs and private consumers and by students and scientists for their research.